Thinking big: How to use theory of change for systems change - Abercrombie, Rob; Boswell, Katie; Thomasoo, Rosanna (NPC, 2018)
We think that, applied well, theory of change can support charities an d funders to take a systemic approach to their work. This report ident ifies five common pitfalls that organisations fall into when using the ory of change, and walks through five rules of thumb that will help or ganisations to use the approach to tackle complex problems. We think t hat, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of cha nge, and walks through five rules of thumb that will help organisation s to use the approach to tackle complex problems.